Crop Insurance Policies Available to Blueberry Growers in Florida - Ariel Singerman; Robert Ranieri (EDIS)
The main source of risk in crop production stems from the unpredictable nature of weather, pests, diseases, etc. By purchasing crop insurance, the farmer transfers part of the risk to an insurance company in exchange for paying a premium (which is the cost of purchasing crop insurance). In this 6-page fact sheet published by the UF/IFAS Food and Resource Economics Department, authors Robert Ranieri and Ariel Singerman describe and provide examples for the two main crop insurance policies available for blueberry farmers in Florida. http://edis.ifas.ufl.edu/fe1054